POWER TO DISSOLVE Ca OXALATE BY LEMON JUICE (Citrus lemon) ON VARIATION OF CONCENTRATION AND IMMERTION TIMES - Endang Triwahyuni Maharani; Jatmiko Susilo; Siva Dwi Kemala Sari (Universitas Muhammadiyah Semarang, 2017)
Lemon juice consisted of 5% citric acid, which gives a distinctive flavor of lemon and gives an pH acidity of about 2-3. Citrate in the lemon juice can be used as a diuretic (laxative urine). Citrate blocks the formation of Ca oxalate or Ca phosphate and form Ca citrate which dissolved in water, so that citrate is able to blocks the kidney stones of calcium production. The purpose of this research is to assess the Ca oxalate solubility by concentration optimization of lemon juice and Ca oxalate weight. From the optimization, the treatment for this research is to marinated the Ca oxalate in lemon juice for 1 hour, 2 hours, and 3 hours, then determine the percentage of the ability of the lemon juice to dissolves Ca oxalate. The result showed that the optimum concentration of the lemon juice (Citrus lemon) is 100%, the optimum weight of Ca oxalate (CaC 2O4) is 1.0 grams and theoptimum lemon juice marinating based on the concentration and the optimum weight is 3 hours, so it can be concluded that the the longer the time Ca oxalate marinated in higher solubility of lemon juice the higher the Ca oxalate. The Ca oxalate dissolved for 1 hour was 21,43% ± 0,11, 2 hours 25,52% ± 0,18 and 3 hours of 42,31% ± 0,09. Key word: Power to dissolve, Lemon juice, citrate, Ca oxalate.